Motivación y productividad de los colaboradores del hipermercado Tottus Oriente Iquitos 2024 - Del Aguila Maldonado, Shirley Estefania (2025)
This study aimed to relate motivation and labor productivity among the employees of Hipermercado Tottus Oriente in Iquitos in 2024. A correlational descriptive design was used, quantitatively focused, implementing a method that avoids experimental approaches and employing a cross-sectional cut, where data was collected at a single point in time. The reliability of the variables was evaluated using Cronbach's alpha, which was 0.841 for motivation and 0.932 for productivity, indicating a high internal consistency of the instruments used. The results showed a Pearson correlation of 0.915** between the variables, with a significance of 0.000, demonstrating a directional and highly significant link. This implies that higher motivation leads to increased productivity among employees. The conclusions emphasize that the findings support the alternative hypothesis, confirming that strategies aimed at improving motivation can have a positive impact on labor productivity.